The Implementation of Parametric Design Practice In Architecture Teaching – How It Can Be Implemented In Indonesia? - Wendy Sunarya; Heru Subiyantoro; Yusvika Ratri Harmunisa; Rizka Tiara Maharani (Center for Scientific Publication, 2022)
Parametric design practice is thriving in the realm of architecture for the last decade. This development is caused by the dynamic progress of computational design technology allowing the designer to engage in complex geometry generation and parametric optimization in the design process. The interoperability of parametric design tool with building simulation software is the key in the parametric design trend that enables designers to solve different socio-environmental problems. Considering of its potencies and development, this study investigates how parametric design practice should be implemented in architecture education, especially in the context of Indonesia university. Reflecting on the teaching case studies in different universities, parametric design should be implemented in architecture teaching, starting from advanced 3D modelling and design fabrication practices. A framework of parametric design teaching is proposed, which can be feasibly implemented in the context of Indonesia university where the awareness of parametric design trend is just growing.